2016
DOI: 10.1159/000452418
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fragmented QRS Complex and Aortic Stiffness in Chronic Hemodialysis Patients

Abstract: Objective: This study aimed to evaluate the correlation between fragmented QRS complex (fQRS), aortic stiffness, and diastolic dysfunction in hemodialysis patients. Subjects and Methods: A sample of 56 patients who received hemodialysis treatment was stratified into 2 groups according to their electrocardiography (ECG) patterns with or without fQRS. Baseline characteristics and laboratory parameters of patients were documented. Conventional echocardiographic and Doppler echocardiographic procedures were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…17 There are two studies investigating the relationship between fQRS and CVD in patients with CKD. 9,18 Adar et al have investigated the relation of fQRS with left ventricular dysfunction in different stages of CKD. 9 The study consisted of 82 CKD patients with normal ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…17 There are two studies investigating the relationship between fQRS and CVD in patients with CKD. 9,18 Adar et al have investigated the relation of fQRS with left ventricular dysfunction in different stages of CKD. 9 The study consisted of 82 CKD patients with normal ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to thank Gülgün for his interest in our paper entitled "Relationship between Fragmented QRS Complex and Aortic Stiffness in Chronic Hemodialysis Patients" [1] . He pointed out that, as one of the important determinants of aortic stiffness, BMI should have been checked in the study population.…”
Section: Dear Editormentioning
confidence: 99%
“…Ferreira et al [5] reported that the mean BMI was higher in subjects with stiffer arteries than those with less stiff arteries based on a longitudinal study, hence their conclusion that blood pressure and the central pattern of body fatness were considerable factors influencing arterial stiffness. However, Güçlü et al [1] did not provide any data regarding BMI in the studied population. Their study would have been more reliable if they had reported that there was no significant difference in BMI between the hemodialysis patients with and without fQRS.…”
mentioning
confidence: 92%
“…giotensin-converting enzyme inhibitors, and angiotensin receptor blockers [1][2][3][4][5] . However, several other factors could have some effect on arterial stiffness.…”
mentioning
confidence: 99%
See 1 more Smart Citation